González González, M. (2019). Funerary Epigrams of Ancient Greece. Reflections on Literature, Society and Religion - Hoz García-Bellido, María Paz de (ARYS. Antigüedad: Religiones y Sociedades, 2020)
GONZÁLEZ GONZÁLEZ, MARTA (2019). Funerary Epigrams of Ancient Greece: Reflections on Literature, Society and Religion. London: Bloomsbury. 224 pp., 74,31€ [ISBN 978-1-3500-6242-9] [Book review]